The impact of dedicated surgical teams on patient outcomes and healthcare cost and delivery: A scoping review with a focus on plastic and reconstructive surgery - Lauren Kiel; C. J. Ernstrom; David M. Le; Lori Silveira; Antonio Porras; Brooke French; Katie Egan; Christodoulos Kaoutzanis; Cindy Barrett; Jason Yu; David W. Mathes; David Khechoyan (Journal of Healthcare Risk Management, 2026)
Abstract Dedicated surgical teams who routinely collaborate may help optimize perioperative outcomes, although team familiarity is often not considered when assessing risk. This review aimed to systematically map evidence regarding dedicated surgical teams and identify knowledge gaps, particularly in plastic and reconstructive surgery (PRS). In a systematic review, of 514 articles screened manuscripts, 72 were included. Eligible studies’ origin, type, specialty, team composition, patient‐centered outcomes, and hospital operational metrics were contextualized collectively and by subspecialty. Collectively, dedicated intraoperative teams were associated with shorter operative times (67%; 18/27), fewer complications (78%; 7/9), less ventilation/cardiopulmonary bypass time (100%; 3/3), lower infection rates (67%; 2/3), reduced blood transfusions (100%; 4/4), and decreased major morbidity (67%; 4/6). Institutional costs decreased (100%; 2/2), readmissions and reoperations decreased (67%; 2/3, 60%; 3/5), hospital and ICU stays shortened (82%; 9/11), and OR turnaround improved (100%; 4/4). Mortality outcomes were mixed (33%; 2/6 significant). Only four studies involved pediatric populations; none included patient‐reported outcomes. Dedicated surgical teams confer patient and hospital benefits. Further research should standardize definitions and prospectively examine outcomes, especially in pediatrics. These findings may be particularly relevant to PRS, where complex multidisciplinary coordination, microsurgical precision, and anesthetic integration require highly synchronized teams.